The Use of Gamal Leaves (Gliricidia sepium) to Accelerate Fresh Fruit Bunch Detachment and Improve the Quality of Crude Palm Oil - Giyanto, Giyanto; Rangkuti, Ika Ucha Pradifta; Raja, Pada Mulia; Winardi, Rafael Remit; Mahyunis, Mahyunis; Ashari, Reza; Elisabeth, Jenny (The University of Lampung, 2024)
Acceleration of processing for fresh fruit bunches (FFB) is crucial to increase profitability and business opportunities for oil palm farmers. This research aims to evaluate the effect of using gamal (Gliricidia sepium) leaves and the duration of ripening on the percentage of FFB processing as well as the quality of crude palm oil. This study employed a factorial completely randomized design (CRD). The data were analyzed using ANOVA with Duncan’s Multiple Range Test at a significance level of 5%. The results of the analysis showed that the best treatment was S3T2 (40% gamal leaves, 20 h of ripening) with a natural processing percentage of 45.87% of the FFB weight and 60.34% of the total bunch weight. The use of gamal leaves and the duration of ripening significantly affected the quality parameters of the oil, especially the free fatty acid content. Treatment S1T1 (20% gamal leaves, 10 h of ripening) showed the best results with a free fatty acid value of 1.30%, meeting the quality standard (<5%). However, the moisture content still exceeded the quality standard (<0.5%), although treatment S3T2 yielded the best result at 0.63%. While, the impurity content quality met the quality standard (<0.5%), with the best value achieved by treatment S1T1 at 0.15%. Keywords: Bunch detachment, CPO quality, Ethylene, Gliricidia sepium, Ripening.